Management of ABC Project through Performance Measurement and Strategy Improvement Determination - Yudha Adi Kusuma; Luqman Ardyansah; Dicy Septian Avandy (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
The success of a project is influenced by effective performance management and the accuracy of improvement strategies. This study aims to measure the performance of the ABC project and determine optimal strategies to enhance efficiency. Performance evaluation is conducted using the performance prism method, which assesses five key aspects: stakeholder satisfaction, stakeholder contribution, strategy, processes, and capabilities. Additionally, the Critical Success Factor (CSF) method is employed to identify the primary factors affecting project success. SWOT analysis is applied to formulate improvement strategies aligned with the project's conditions. Data collection is carried out through surveys, interviews, and in-depth analysis of the project conditions. The results indicate that the process aspect holds the highest weight in the execution of the ABC project, while the final inspection activity is the dominant factor in determining its success. Based on the analysis, 12 improvement strategies have been identified to enhance efficiency and mitigate project delays. These strategies include process optimisation, technology implementation, and improved stakeholder coordination. The findings of this study are expected to contribute to project management in optimising performance, enhancing resource management effectiveness, and supporting more efficient and competitive project execution.